CORRELATION BETWEEN COMPLIANCE WITH IRON TABLET CONSUMPTION AND IRON NUTRITION INTAKE WITH PREGNANT WOMEN'S HEMOGLOBINE CONSUMPTION - Novi Dwi Ambarsari; Netti Herlina; Linda Dewanti; Ernawati (Universitas Airlangga, 2023)
Introduction: During pregnancy, the need for iron increases, which triggers anemia. Anemia can be described as a decline in the hemoglobin level below a critical level. Meanwhile, based on a preliminary study, 10 out of 13 pregnant women were not obedient in taking iron tablets (76, 92%). The prevalence of anemia at Tanah Kalikedinding Community Health Center in 2015 remained high. Method: The analytical study used a cross-sectional design. The group of pregnant women in the third trimester who received Fe tablets and had their Hb levels checked at the Tanah Kalikedinding Health Center Surabaya were 54 people. The sampling technique chosen was total sampling. The instruments used were questionnaire sheets, data collection sheets, and survey software. Data analysis used the Fisher exact test. Result : Out of the 54 pregnant women, 20.4% of pregnant women were obedient to taking blood-supplement pills and experienced an increase in hemoglobin levels (63.3%), 70.6% of pregnant women were not adherent, and almost all of them had decreased their. The results of a bivariate analysis using Fisher's exact showed a significance value of p-value = 0.001 <α = 0.05 (p <α). Conclusion: This meant a correlation between adherence to consuming Fe tablets and hemoglobin levels in pregnant women. Also, a p-value of 0.001 (p <α). This means there is a correlation between iron nutritional intake and consumption of blood-supplemented tablets and hemoglobin gravida levels at Puskemas Tanah Kalikedinding, Surabaya.